PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ICT PADA MATA PELAJARAN TAHSIN ALQURAN DI MADRASAH ALIYAH ANNUR PRIMA MEDAN - Muhammad Panjaitan, Pratama; Harfiani, Rizka; Amini, Amini (Berajah Journal, 2025)
This study aims to develop ICT (Information and Communication Technology)-based learning media for the Tahsin Al-Qur'an subject at Madrasah Aliyah Annur Prima Medan. This study uses a descriptive qualitative method with the Hannafin and Peck development model which includes three stages, namely design, needs analysis, development and implementation. The results of the study indicate that the developed learning media are feasible in terms of content, appearance, and ease of use. The results of the study indicate that this media is relevant to learning needs and makes it easier for students to understand the tahsin al-Qur'an material. These findings indicate that ICT-based learning media can be an innovative solution in improving the quality of Tahsin learning in Madrasas